Oxford studies in metaethics. Volume 7 - Shafer-Landau, Russ. (Oxford : Oxford University Press, 2012)
'Oxford Studies in Metaethics' is devoted to original philosophical work in the foundations of ethics. It provides an annual selection of much of the best new scholarship being done in the field.
Description based on online resource; title from home page (viewed on July 13, 2012).
Includes bibliographical references and index.
Keywords: Ethics